Electron microprobe analysis and Ar-Ar age dating of polyhalite from the evaporitic Permian Haselgebirge Formation - Leitner, Christoph; Neubauer, Franz; Genser, Johann; Bernroider, Manfred (PANGAEA, 2022)
To test polyhalite age dating of the mineral polyhalite [K2Ca2Mg(SO4)4·2H2O], samples of the evaporitic Permian Haselgebirge Formation were collected in the Eastern Alps. Samples were taken from two salt bodies. The salt body of Altaussee (UTM 33T 405316 5278325) has a vertical thickness of >800 m. Samples were collected in the Altaussee mine (ALT). The salt body of Bad Dürrnberg-Berchtesgaden (UTM 33T 351091 5278007) is at least 1000 m thick. The salt body comprises two separate mines, where samples were collected, Bad Dürrnberg (DÜ) and Berchtesgaden (BGD) salt mines. The samples were collected during several field trips, and investigated at the University of Salzburg during the years 2007-2015. Electron microprobe analyses were conducted to determine possible chemical variations of polyhalite.
Keywords: age dating; Eastern Alps; Haselgebirge; polyhalite